Usability Testing Website Pelayanan Publik SILETON Kabupaten Agam Dengan Metode SEQ dan SUS - Abrory, Yudhistira; Kamil, Wafiq Alfin; Zahrati, Wenty (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2025)
Digital transformation has become an inevitable global agenda, with the Government of Indonesia competing to integrate technology into public services. In the local scope, Agam Regency has responded to this initiative through the SILETON website, which is a form of digitization of population administration and civil registration. This research aims to provide in-depth insight into the performance of SILETON applications from a use perspective through quantitative methods and qualitative verbalization of SEQ and SUS models. The results of research and analysis of usability evaluation on the SILETON application in SEQ testing, with a mean of 6.4 out of 7, with verbalization by 10 respondents, and the SUS method obtained a score of 74.22, and the adjective rate was good. Based on this study was found that overall the SILETON website is considered to have a good level of usability and is quite satisfactory for users, with several recommendations for improving service features.